(untitled) (Global Journal of Science Frontier Research, 2012)
The paper begins by stating and illustrating what it claims as a new discovery, namely, that the refractive index of a substance is a function of the gravitational field set up by its molecules. An interpretation of the discovery leads to revolutionary insights on the nature of refraction and the relationship linking space, mass and energy. A nanotechnology based on this discovery is suggested.